(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The frequency of occurrence of variants of the development of the structure of cerebral vessels in patients with Kimmerle anomaly was studied. 67 patients with Kimmerle anomaly were examined, aged from 16 to 60 years, average age 40±5 years; 55 women – 82.0% and 12 men – 18%. All subjects underwent MSCT of the brain with capture and 3D craniovertebral junction and MR angiography. Correlative data of radiological and clinical signs were determined with subsequent statistical processing. It has been determined that in most cases with Kimmerle’s anomaly there are anomalies in the development of cerebral vessels.